DOUBLE GLAZING AND METHOD FOR MANUFACTURING SAME - HASEGAWA, KAZUYA (2016)
This double glazing (1) comprises: a pair of glass plates (10, 11) arranged facing each other; a separator (20) which is arranged along the periphery of the pair of glass plates (10, 11) and separates glass plate (10) and glass plate (11); a through hole (30) through which an inner space (12) communicates with the outer space, the inner space (12) being formed by the pair of glass plates (10, 11) and the separator (20); and an ultraviolet curable resin (40) which is provided inside the through hole (30) and seals the inner space (12). The inner space (12) is filled with inert gas. L'invention concerne un double vitrage (1) qui comporte : une paire de plaques de verre (10, 11) agencées l'une en face de l'autre ; un séparateur (20) qui est agencé le long de la périphérie de la paire de plaques de verre (10, 11) et qui sépare la plaque de verre (10) et la plaque de verre (11) ; un trou traversant (30) à travers lequel un espace intérieur (12) communique avec l'espace extérieur, l'espace intérieur (12) étant formé par la paire de plaques de verre (10, 11) et le séparateur (20) ; une résine pouvant durcir aux ultraviolets (40) qui est disposée à l'intérieur du trou traversant (30) et qui scelle l'espace intérieur (12). L'espace intérieur (12) est rempli d'un gaz inerte. 複層ガラス（１）は、互いに対面して配置された一対のガラス板（１０、１１）と、一対のガラス板（１０、１１）の周に沿って配置されて、ガラス板（１０）とガラス板（１１）とを離間させる離間材（２０）と、一対のガラス板（１０、１１）と離間材（２０）とによって形成される内部空間（１２）と外部空間とを連通する貫通孔（３０）と、貫通孔（３０）内に設けられて内部空間（１２）を封止する紫外線硬化樹脂（４０）とを備え、内部空間（１２）には、不活性ガスが充填されている。